Determining the Impact of By-O-Reg+ in Diets with or without a Feed Grade Antibiotic on Growth Performance of Nursery Pigs - L. L. Thomas; J. C. Woodworth; R. D. Goodband; J. M. DeRouchey; M. D. Tokach; S. S. Dritz (Kansas Agricultural Experiment Station Research Reports, 2015)
A total of 717 nursery pigs (PIC C-29 × 28 and PIC L3-1050 × 1040, initially 12.48 ± 0.10 lb) from two consecutive nursery groups were used in a 35-d growth study. The objective was to determine the impact of increasing levels of By-O-Reg+ in diets with or without 50 g/ton Carbadox. By-O-Reg+ is a unique mixture of essential oils primarily based on oregano. It utilizes encapsulation technology to stabilize the essential oils and is suggested to have antimicrobial-like properties. The present study evaluated growth performance of nursery pigs fed 1 of 6 dietary treatments that were arranged as a 2 × 3 factorial with main effects of antibiotic (none vs. 50 g/ton Carbadox) and By-O-Reg+ (0, 1, or 2 lb/ton). Experimental diets were fed for 21 d and then a common diet was fed for the final 14 d. Pens of pigs (5 barrows and 5 gilts) were balanced by initial BW and randomly allotted to treatments, with 12 replications (pens) per treatment. During the period when treatments were fed (d 0 to 21) no interactions were observed between By-O-Reg+ and Carbadox. Increasing By-O-Reg+ decreased, and then increased (quadratic P = 0.016) F/G. Pigs fed diets with Carbadox had improved (P<0.007) ADG, ADFI, and F/G. From d 21 to 35, when a common diet was fed, pigs previously fed diets with Carbadox had increased (P = 0.007) ADFI. However, an interaction (linear, P = 0.039) was observed with pigs previously fed diets without Carbadox showing decreased ADFI as By-O-Reg+ increased; whereas when pigs were previously fed diets containing Carbadox, ADFI increased as the level of By-O-Reg+ increased. For the overall period (d 0 to 35), an interaction (linear, P = 0.031) was observed for ADFI with pigs fed diets without Carbadox having decreased ADFI as By-O-Reg+ increased; whereas when pigs were fed diets containing Carbadox, ADFI increased with increasing By-O-Reg+. No main effects of By-O-Reg+ were observed for the overall data; however, adding Carbadox for 21 d after weaning improved (P<0.015) ADG, ADFI, and final BW and tended to improve (P<0.087) F/G. Overall, this study confirms the benefit of including a feed grade medication in nursery pig diets to improve growth performance. Increasing By-O-Reg+ in diets elicited few changes in performance, but during the test period the pigs fed 1 lb/ton of By-O-Reg+ had better F/G than those fed none or the 2 lb/ton of By-O-Reg+. More research is needed to confirm if 1 lb/ton inclusion of By-O-Reg+ is the appropriate dose to elicit the best response.
Keywords: antibiotics; nursery pigs; oregano